Unsur-unsur yang Mempengaruhi Penerimaan dan Penolakan Terhadap Perubahan Manajemen Organisasi - M. As Alukal Huda Mei Fani (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In an era of dynamic change, organizations must be able to adapt and implement changes to stay relevant and compete in an ever-evolving market. However, organizational change is often faced with acceptance and rejection from members of the organization. Acceptance of change reflects the positive attitude shown by the individual towards the proposed change, while resistance to change describes the negative attitude or resistance shown by the individual towards the change. An understanding of the elements that influence the acceptance and rejection of organizational change is important for managers and decision makers in facing the challenges of organizational change. In this study the authors used a qualitative research method approach. This research aims to achieve success in implementing change, effective change management must be implemented. Acceptance or resistance to change management in an organization is influenced by factors such as effective communication, employee engagement, perceptions of fairness, social influence, uncertainty, sense of security, and effective leadership. Understanding and managing these elements well can increase the chances of successful change and reduce resistance.